PENGARUH INTERAKSI SOSIAL DISEKOLAH TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS X SMK MANDIRI PONTIANAK - Desinta, Desinta; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractRelationships with importance are always related to communication and relationship terms. Basically, humans need interaction in interactions, interactions in families, communities, and schools. A person's development and motivation is also a process that gives encouragement and encouragement.So this study aims to get information and describe about Social Influence in Schools Against Learning Motivation of Class X Learners of Independent SMK Pontianak. While the specific purpose is to know (1) Motivation to learn students of class X Mandiri SMK. (2) What is the social interaction of students in the X class of Mandiri Vocational School. (3) Knowing the social interactions of students in the school towards the learning motivation of students in class X Mandiri SMK. The method used is descriptive method and form of survey research. The population in this study were 149 and a sample of 21 students of the Pontianak Independent Vocational School. This research uses quantitative. The technique of collecting data with questionnaires while the data analysis technique uses the percentage formula.Based on the results of this study, the dominant social interaction reached 93% with the category "Good" while the dominant learning motivation extrinsic motivation reached 91% with the category "Good". Based on the research using the Pearson hierarchy discussion method, the coefficient ratio figures obtained rs = 0.967. This indicates a change. Can be concluded as "social interaction with students' learning motivation in class X Vocational School Mandiri Pontianak "Keywords:Social Interaction, Learning Motivation